Critical shortage of capacity to deliver safe paediatric surgery in sub-Saharan Africa: evidence from 67 hospitals in Malawi, Zambia, and Tanzania - Gajewski, Jakub; Pittalis, Chiara; Borgstein, Eric; Bijlmakers, Leon; Mwapasa, Gerald; Cheelo, Mweene; Juma, Adinan; Sardana, Muskan; Brugha, Ruairi (Frontiers in Pediatrics, 2023)
Introduction: Paediatric surgical care is a significant challenge in Sub-Saharan Africa (SSA), where 42% of the population are children. Building paediatric surgical capacity to meet SSA country needs is a priority. This study’s aim was to assess district hospital paediatric surgical capacity in three countries: Malawi, Tanzania and Zambia (MTZ). Methods: Data from 67 district-level hospitals in MTZ were collected using a PediPIPES survey tool. Its five components are procedures, personnel, infrastructure, equipment, and supplies. A PediPIPES Index was calculated for each country and a two-tailed analysis of variance test used to explore cross-country comparisons. Results: Similar paediatric surgical capacity index scores and shortages were observed across countries, greater in Malawi and less in Tanzania. Almost all hospitals reported capacity to perform common minor surgical procedures and less complex resuscitation interventions. Capacity to undertake common abdominal, orthopaedic and urogenital procedures varied - more often reported in Malawi and less often in Tanzania. There were no paediatric or general surgeons or anaesthesiologists at district hospitals. General medical officers with some training to do surgery on children were present (more often in Zambia). Paediatric surgical equipment and supplies were poor in all three countries. Malawi district hospitals had the poorest supply of electricity and water. Conclusions: With no specialists in district hospitals in MTZ, access to safe paediatric surgery is compromised, aggravated by shortages of infrastructure, equipment and supplies. Significant investments are required to address these shortfalls. SSA countries need to define what procedures are appropriate to national, referral and district hospital levels; and ensure that an appropriate paediatric surgical workforce is in place at district hospitals, trained and supervised to undertake these essential surgical procedures so as to meet population needs.